Management of Sports Tournaments with The Support of Information and Communication Technologies - Gabriel KOMAN; Martin HOLUBČÍK; Jakub SOVIAR (Communications of International Proceedings, 2023)
With the Development of ICT, IT is Possible to Shift Efficiency and Decision-Making Even in Sport and ITS Management. Data Can Be Stored and Communicated Through ICT, Making Them Easy To View, Work With Better, And Also Share or Make Them Them Available to The Public. The purpose of the article is to analyze and describe the playing interconnection between sports events management and using ICT technologies to help them in sustainability and constant improvement. The analysis of opponents and future or ongoing tournaments is Simpler and Fairer, More Accessible for More Significant Preparation and, Finally, Better Quality Play. From these analyzes, the lack of use of ICT technologies, which could be significantly higher and more extensive, disappeared. In this article, the methodology of content analysis and case studies analysis is used. ICT Contributes to Information for Different Sports, But Equally ICT Involved in Sports Processes Makes Available Data and Interesting Use or Experience for Spectators and Sports Enthusiasts. The Aim of This Article is to Bring Closer the Use of Information and Communication Technologies in Sports. As a result, Smart Stadiums are the best way to be ICT in sport beneficial for organizers of events, athletes and spectators.
Keywords: sport; information communication technology; management